PENGARUH LIKUIDITAS, SOLVABILITAS, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Sub Sektor Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - , Eka Hariyani, Aghnan Kamemy , Andreas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of liquidity, solvency, company size and company age on audit report lag in food & beverage companies in 2017-2019 which are listed on the IDX. The research method used is quantitative with secondary data in the form of financial report data on the IDX with a sample of 15 food & beverage companies. This study uses multiple linear regression analysis techniques. The results of this study indicate that the independent variables liquidity, solvency, firm size and firm age are the dependent variable audit report lag. Keywords : Liquidity, Solvency, Company Size, Company Age, Audit Report Lag